2013
DOI: 10.1051/0004-6361/201321288
|View full text |Cite
|
Sign up to set email alerts
|

A normal abundance of faint satellites in the fossil group NGC 6482

Abstract: A fossil group is considered the end product in a galaxy group's evolution. It is a massive central galaxy that dominates the luminosity budget of the group, and is the outcome of efficient merging between intermediate-luminosity members. Little is known, however, about the faint satellite systems of fossil groups. Here we present a Subaru/Suprime-Cam wide-field, deep imaging study in the B− and R−bands of the nearest fossil group NGC 6482 (M tot ∼ 4 × 10 12 M ), covering the virial radius out to 310 kpc. We p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 61 publications
(111 reference statements)
2
25
0
Order By: Relevance
“…For z 0.2, the mean number of faint galaxies in fossil systems grows to finally reach the values observed in control groups at z = 0. This later result agrees with the observational work of Lieder et al (2013), who found a normal abundance of faint satellites in the NGC 6482 fossil group. This rapid growth in the number of faint galaxies could be a consequence of a smaller number of missing galaxies in fossils.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…For z 0.2, the mean number of faint galaxies in fossil systems grows to finally reach the values observed in control groups at z = 0. This later result agrees with the observational work of Lieder et al (2013), who found a normal abundance of faint satellites in the NGC 6482 fossil group. This rapid growth in the number of faint galaxies could be a consequence of a smaller number of missing galaxies in fossils.…”
Section: Discussionsupporting
confidence: 92%
“…Using this definition, it is assumed that galaxies within half the virial radius have had time to merge within a Hubble time, and also that normal elliptical galaxies that are not located at the centre of the groups will not be chosen as potential fossil groups (Lieder et al 2013). In addition to the conventional criteria, there exists an alternative criterion developed by Dariush et al (2010).…”
Section: Fossil Groupsmentioning
confidence: 99%
See 1 more Smart Citation
“…This agrees with our general result that the faint-end slope increases with the gap in magnitude. In a recent work, Lieder et al (2013) analyzed the FG NGC 6482. They present a deep spectroscopic LF, down to M r = −10.5.…”
Section: Comparison With the Literaturementioning
confidence: 99%
“…They found that the LF of these objects are well fitted by single Schechter function, but there is a large variety of values in the faint-end slope (α) of the LFs of FGs. In particular, the values of α measured goes from −1.6 to −0.6 (see Cypriano et al 2006; Khosroshahi et al 2006;Mendes de Oliveira et al 2006Zibetti et al 2009;Aguerri et al 2011;Lieder et al 2013). Unfortunately, all these studies were performed on single FGs or very small samples, and a systematic study of LFs of statistically meaningful samples of FGs remains to be done.…”
Section: Introductionmentioning
confidence: 98%